2022
DOI: 10.1007/s40265-022-01803-2
|View full text |Cite
|
Sign up to set email alerts
|

Should We Interfere with the Interleukin-6 Receptor During COVID-19: What Do We Know So Far?

Abstract: Severe manifestations of COVID-19 consist of acute respiratory distress syndrome due to an initially local reaction leading to a systemic inflammatory response that results in hypoxia. Many therapeutic approaches have been attempted to reduce the clinical consequences of an excessive immune response to viral infection. To date, systemic corticosteroid therapy is still the most effective intervention. More recently, new hope has emerged with the use of interleukin (IL)-6 receptor inhibitors (tocilizumab and sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 178 publications
0
6
0
Order By: Relevance
“…The narrative review reported by Plocque and colleagues [ 1 ] elegantly discussed if interleukin-6 (IL-6) receptor inhibitors should be used in the management of coronavirus disease 2019 (COVID-19). Undeniably, as discussed by the authors, the interruption of the IL-6 pathway by administering IL-6 receptor inhibitors, especially tocilizumab, could reduce the risk of mortality in patients with COVID-19 who are high-flow oxygen-dependent as well as patients with COVID-19 who have recently been admitted to the intensive care unit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The narrative review reported by Plocque and colleagues [ 1 ] elegantly discussed if interleukin-6 (IL-6) receptor inhibitors should be used in the management of coronavirus disease 2019 (COVID-19). Undeniably, as discussed by the authors, the interruption of the IL-6 pathway by administering IL-6 receptor inhibitors, especially tocilizumab, could reduce the risk of mortality in patients with COVID-19 who are high-flow oxygen-dependent as well as patients with COVID-19 who have recently been admitted to the intensive care unit.…”
mentioning
confidence: 99%
“…Nevertheless, despite their mortality benefits, the potential risks associated with IL-6 receptor inhibitors during the management of COVID-19 are still unclear. In their review, the authors have discussed the potential increased risk of nosocomial infections [ 1 ]. We intend to complement their discussion by raising another perspective that should be considered while using IL-6 receptor inhibitors in patients with COVID-19.…”
mentioning
confidence: 99%
“…This underlined the assumption that COVID-19 was comparable to sepsis and led to the idea that these biomarker levels were the cause for organ failure and, thus, needed to be suppressed [16][17][18][19][20][21]. Therefore, several clinical trials started using anti-inflammatory therapies to try to reduce the cytokine plasma levels [22][23][24] (Table 2). These clinical trials have not been successful so far and, in some cases, have even worsened patient outcomes [25,26].…”
Section: Covid-19-induced Sepsis Immunotherapies and Antiviral Treatm...mentioning
confidence: 99%
“…High IL-6 levels exert pleiotropic effects on the immune system through cis-signaling, resulting in cytokine release syndrome (CRS) [ 24 ]. IL-6 inhibitor has been shown to be effective in patients with severe COVID-19 and have become one of the standard treatments against COVID-19, but the best beneficiary group needs to be evaluated [ 25 ].…”
Section: Covid-19 Immunologymentioning
confidence: 99%